Finite analysis of stability between modified articular fusion technique, posterior lumbar interbody fusion and posteriorlateral lumbar fusion - Xiao Han (BMC, 2021)
Abstract Background It is not clear whether modified facet fusion (MFF) is biomechanically different from traditional fusion techniques such as posterior lateral lumbar fusion (PLF) and posterior lumbar interbody fusion (PLIF). Methods In this study, a healthy adult Chinese male volunteer was selected to perform 3D reconstruction of CT image data and simulate the successful fusion of L4–5 MFF, PLF and PLIF, respectively. The motion range of L4–5 segments of the model was simulated under 6 working conditions, including forward flexion, extension, lateral flexion and rotation under normal physiological conditions, and the stability of the three fusion procedures in the pathological segments of the lumbar spine was compared. Results There was no difference in range of motion between MFF model and PLF or PLIF model (P < 0.05). Also, the stiffness of the PLFand the MFF model were comparable (P > 0.05), but were smaller than the PLIF model (P < 0.05). Conclusions MFF provides reliable stability at the lumbar fixation fusion level and does not differ significantly from PLF and PLIF in terms of range of motion.